The Socio-Economic Impacts of the Porong Mud Volcano on the Shrimp Fisheries Sector in Sidoarjo District, East Java Province, Indonesia - Fitrianto, Achmad Room (Curtin University, 2019)
This thesis analyses the socioeconomic impact of the Sidoarjo mud volcano on shrimp fisheries’ production. It adapts the sustainable livelihoods framework in order to investigate how local livelihood assets are utilised to maintain and adapt livelihood strategies in response to river pollution in the context of a local and globalised aquaculture industry.